IGNORE A CHILD’S EMOTIONAL NEEDS’ EFFECT ON ADULT LIFE - Anwari Khatun (International Journal of Multidisciplinary Research and Studies, 2021)
Despite being the most common type of child abuse, neglect's correlations and effects are little known, especially in relation to early adulthood. In order to fill this vacuum in the research, the current multi-wave longitudinal study looked at physical and emotional neglect in emerging adults in a broad community sample. In a three-year study, 580 adolescents (AgeMean = 18.25; AgeSD = 0.59; 58.3% female; 31% Hispanic; 28.9% Caucasian; 26.2% African-American; 13.9% other) completed self-report tests for child maltreatment at baseline as well as tests for depression, posttraumatic stress disorder, generalised anxiety disorder, and substance use. In order to better understand a) how physical and emotional neglect relate to other types of maltreatment and b) how physical and emotional neglect specifically affects future mental health functioning, we conducted our analyses using both variable-centered (mixed-level modelling) and person-centered (latent profile analysis) analyses.